Inflammation predicts new onset of depression in men, but not in women within a prospective, representative community cohort - Ernst, Mareike (Sci Rep, 2021)
Depression has been associated with increased inflammation. However, only few large-scale, prospective studies have evaluated whether inflammation leads to new cases of depression and whether this association can be found in men and women. Longitudinal data of N = 10,357 adult participants with no evidence of depression at baseline (based on Patient Health Questionnaire (PHQ-9), lifetime diagnoses, and current antidepressant medication) were evaluated for depression 5 years later. Multivariate logistic regression models were used to predict the onset of depression based on C-reactive protein (CRP) and white blood cell count (WBC). We used interaction terms and separate analyses in men and women to investigate gender-dependent associations. Based on both markers, inflammation was predictive of new cases of depression 5 years later, even when adjusting for sociodemographic, physical health, health behavior variables, and baseline depression symptoms. As established by interaction terms and separate analyses, inflammatory markers were predictive of depression in men, but not in women. Additional predictors of new onset of depression were younger age, loneliness, smoking (only in men), cancer and less alcohol consumption (only in women). The study indicates gender differences in the etiology of depressive disorders within the community, with a greater role of physical factors in men.